Is it law really known to all? Language barriers as a limitation of the accessibility to national and international regulations in the Peruvian legal system - Velásquez Barrionuevo, Alejandro José (2020)
The purpose of this paper is to analyze whether law is indeed a type of knowledge that should be presumed to be known or not known by all. Based on a review of various authors and standards, language barriers against the possibility of effective access to various types of national and international regulations are identified. Finally, some solutions to the above-mentioned problems are proposed.